Biogenic Gold Nanoparticles Decrease Methylene Blue Photobleaching and Enhance Antimicrobial Photodynamic Therapy - Irena Maliszewska (Molecules, 2021)
Antibiotic resistance is a growing concern that is driving the exploration of alternative ways of killing bacteria. Here we show that gold nanoparticles synthesized by the mycelium of Mucor plumbeus are an effective medium for antimicrobial photodynamic therapy (PDT). These particles are spherical in shape, uniformly distributed without any significant agglomeration, and show a single plasmon band at 522–523 nm. The nanoparticle sizes range from 13 to 25 nm, and possess an average size of 17 ± 4 nm. In PDT, light (from a source consisting of nine LEDs with a peak wavelength of 640 nm and FWMH 20 nm arranged in a 3 × 3 array), a photosensitiser (methylene blue), and oxygen are used to kill undesired cells. We show that the biogenic nanoparticles enhance the effectiveness of the photosensitiser, methylene blue, and so can be used to kill both Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria. The enhanced effectiveness means that we could kill these bacteria with a simple, small LED-based light source. We show that the biogenic gold nanoparticles prevent fast photobleaching, thereby enhancing the photoactivity of the methylene blue (MB) molecules and their bactericidal effect.